PERANCANGAN MOTION GRAPHIC SEJARAH KERAJAAN MAJAPAHIT DARI TERBENTUK HINGGA MASA KEJAYAAN - MUHAMMAD ROZI ROSANDI, Dini Faisal, S.Ds., M.Ds., Drs. Ariusmedi, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Nowadays there are a lot of entertainment media that raise historical themes abroad, such as games, animation, movies, and comics. Communities in Indonesia, especially many adolescents who are interested in foreign history themes, they know who the historical figures and events that occurred in its history. But domestic history is being abandoned due to a lack of interest in youth in local history and a lack of media that raises historical themes.The purpose of designing the motion graphic history of the Majapahit empire from being formed to its glory is to attract teenagers to domestic history. The theme of Majapahit is raised because Majapahit's history is very well known in Indonesia but currently there are not many teenagers who know the story. The designer chooses motion graphic media because of its simple nature so that it is effective in attracting interest and the manufacturing process that is not as difficult as other media entertainments so that it is fast in design.The method used in the motion graphic design is by interviewing the history teacher and looking for data from a book by Slamet Muljaya. The author designs motion graphics and is supported by supporting media in the form of x-banners, trading cards, mugs, clocks, stickers, totebags, and t-shirts, which are able to promote Motion Graphic History of the Majapahit Empire from Formed to Glory.Keywords: Motion Graphic, History, Majapahit